세포 내 지방생성과 Glut-4 의존성 포도당 운반에 미치는 발효복합한약 물추출물(F-MAPC)의 영향 - 전서영; Seo Young Jeon; 박지영; Ji Young Park; 김성옥; Sung Ok Kim; 이은실; Eun Sil Lee; 구진숙; Jin Suk Koo; 김미려; Mi Ryeo Kim (大韓本草學會誌, 2014)
Objectives : The aim of this study was to investigate the effects water extract of fermented new korean medicinal mixture, combinations of Mori Folium, Adenophorae Radix, Phllostachyos Folium and Citri Pericarpium (F-MAPC), on adipocyte differentiation, adipogenesis and glucose uptake using undiffernentiated 3T3-L1 adipocytes and L6 myoblasts. Methods : Each herb and those mixture were respectively fermented and then extracted with water. We carried on MTT assay for check-up on cell toxicity, Oil Red O staining for determination of cell differentiation and intracelluar adipogenesis. Western blot analysis for measurement of pAMPK and pACC, C/EBPα, PPARγ and Glut-4 protein expressions were performed. Results : F-MAPC showed significant inhibitory activity on adipocyte differentiation in 3T3-L1 preadipocytes without affecting cell toxicity as assessed by measuring fat accumulation, and this effect was 2 fold higher in 0.2 mg/ml F-MAPC than that of the same dose of each fermented herbal extract alone. In addition, these effects were associated with modulation of adipogenic transcription factors, such as C/EBPα, PPARγ, as well as stimulated phosphorylations of AMPK and ACC. Translocation of Glut-4 was significantly increased by 10.2% in L6 cells treated with 0.2 mg/ml F-MAPC compared with that of control. Conclusions : These results demonstrate that F-MAPC may be an ideal candidate for therapy of obesity and diabetes by disturbing the differentiation into adipocytes, as well as the inducement of intramuscular glucose uptake from blood.